2020
DOI: 10.25105/urbanenvirotech.v4i1.7151
|View full text |Cite
|
Sign up to set email alerts
|

Urban Facade Geometry on Outdoor Comfort Conditions: A Review

Abstract: <p>Designing urban facades is considered as a major factor influencing issues<br />such as natural ventilation of buildings and urban areas, radiations in the<br />urban canyon for designing low-energy buildings, cooling demand for<br />buildings in urban area, and thermal comfort in urban streets. However, so<br />far, most studies on urban topics have been focused on flat facades<br />without details of urban layouts. Hence, the effect of urban facades with<br />deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In previous studies, it was found that the aesthetics, color and interface permeability of building façades [71,72] can improve street comfort under the same pattern of spatial building layout. Research attention has also been paid to the relationship between the texture and form of building façade and human visual evaluations [73]. In addition, the use of 'terrain' is an important design approach to enhance spatial interest [74], which may explain its positive influence on street comfort in this study.…”
Section: Design Implications Based On Comfort-related Street Indicato...mentioning
confidence: 97%
“…In previous studies, it was found that the aesthetics, color and interface permeability of building façades [71,72] can improve street comfort under the same pattern of spatial building layout. Research attention has also been paid to the relationship between the texture and form of building façade and human visual evaluations [73]. In addition, the use of 'terrain' is an important design approach to enhance spatial interest [74], which may explain its positive influence on street comfort in this study.…”
Section: Design Implications Based On Comfort-related Street Indicato...mentioning
confidence: 97%
“…We believe that improving and enhancing the visual comfort of the color environment can have psychological, physical, and health impacts. Furthermore, visual comfort is considered a major factor affecting issues such as low-energy architectural design and urban street thermal comfort [56]. Designers can leverage this understanding to delve deeper into visual comfort within the ecological environment.…”
Section: Effects Of Luminance Contrast (Vc) and Chromaticity Contrast...mentioning
confidence: 99%
“…The use of a reflective façade, though it might be beneficial for the indoors, may cause glare that is unpleasant, even harmful, for the outdoor dwellers [8,43,59]. Another factor contributing to reflected glare in the outdoor environment is the building geometry-the form of individual buildings and the overall relationship between neighboring buildings [59,60]. Reflected glare is best avoided by minimizing the use of reflective surfaces-using flat or matte finishes instead-and by working with geometry, such as adjusting the angle of reflective materials to diffuse the reflection [12,59].…”
Section: Human Comfort In the Outdoor Environmentmentioning
confidence: 99%